A Literature Review: Effectiveness of Swedish Foot Massage Therapy on Quality of Sleep in Elderly with Essential Hypertension - Rahmah Widyaningrum; Tri Hadi Miftahul Ulum; Anis Dwi Yulianti (Universitas Ahmad Dahlan, 2023)
Background: Aging processes in the elderly lead to degenerative diseases, one of them being essential hypertension. The elderly with hypertension often complain about sleeping problems, difficulty staying awake, often waking up in the middle of the night, and later difficulty going back to sleep, waking up too early, and sleeping poorly. Treatment of sleeping problems may include pharmacology and non-pharmacology. One nonpharmacological treatment was a complementary therapy called foot massage with Swedish techniques. The purpose is to determine the effect of Swedish foot massage therapy on sleep quality in the elderly with essential hypertension. Method: Literature Review. Data Sources: Science Direct, Springer Nature, Hindawi, Researchgate, and Sinta. The research method used is Literature Review with the PICO Analyst method (Problem, Intervention, Comparison, and Outcome) from 2011 to 2021 with the keywords